Facile one-pot hydrothermal approach for the preparation of CuO/rGO nanocomposites with different morphologies - Ajit, Akshata V.; Gawli, Yogesh P.; Ethiraj, Anita Sagadevan (API Conference Proceedings, 2018)
Graphene-based metal oxides such as Cu2O, SnO2, CuO, Fe3O4, MnO2 are promising candidates for many applications because of their advantageous properties. Amongst all, CuO has been widely studied because of its excellent electrocatalytic activity. Although many methodologies have been developed for the synthesis of CuO/graphene nanostructures with different morphologies including nanorods, nanoparticles, nanosheets, flower, urchin; not many investigations have been done on one pot synthesis method for CuO/reduced graphene oxide (rGO) nanocomposites to achieve different morphologies. Therefore in the present work effort has been made to synthesize various CuO-rGO nanocomposites via surfactant (CTAB) assisted hydrothermal method. Detailed study was performed to monitor the effect of various reaction parameters like temperature, reaction time, reactant concentration on the synthesized nanocomposites. Several analytical tools, including XRD, SEM, FTIR and UV-Vis spectroscopy have been utilized to characterize the samples. XRD results showed formation of monoclinic structure of CuO along with presence of rGO. Calculated optical bandgap studies indicate decrease in the bandgap of synthesized CuO (Eg=4.5eV-4.34eV) with increase in temperature from 120°C to 180°C. Our results clearly demonstrate that reaction parameters play a key role to bring out the optical and morphological changes in the CuO-rGO nanocomposites.